Central diabetes insipidus following minor head trauma in a child with normal neuroimaging - Kumari, Neetu; Kumari, Neha; Azam, Nazifa (International Journal of Contemporary Pediatrics, 2026)
Central diabetes insipidus (CDI) is an uncommon endocrine consequence of head injury in children and is typically associated with moderate to severe trauma. Development of CDI after trivial head injury, particularly in the presence of normal neuroimaging, is rare and may be easily overlooked. We report a 4-year-old child who presented with polyuria and polydipsia following a minor head injury, with laboratory findings consistent with central diabetes insipidus and normal magnetic resonance imaging of the brain. Prompt initiation of desmopressin resulted in rapid clinical improvement. This case emphasizes the need for clinical vigilance for CDI in children presenting with unexplained polyuria even after apparently insignificant head trauma.